Edukasi Logo Obat, Dagusibu dan Bud Serta Cek Kesehatan Guru - Yulion, Rizky; Mitra, Aisa Dinda; Asadi, Henityo Agung; Amanda, Regina; Gunawan, Indra; Dewansyah, Ahmad Rozan; Novira, Tita Aulya (Universitas Baiturrahim, 2024)
Community service activities were carried out at SMA N 1 Muaro Jambi with the educational theme of drug logos, dagusibu, and Beyorn Use Date (BUD) as well as free health checking activities for educators at SMA N 1 Muaro Jambi. The topic was raised to provide education delivery to respondents with formal education and is expected to have a positive impact on the surrounding location. The topic also supports the program of the Central Board of the Indonesian Pharmacists Association (PP-IAI). This activity was carried out by making 10 questions designed that referred to the theme and topic of the activity consisting of pre-test and post-test, the next data was carried out through statistical tests using Paired T-tests. Tangible differences were obtained in respondents who received educational exposure (P<0.05). With data on 23 respondents, There is an increase in the educational value of respondents on community service materials. These results also confirm the understanding of the material educational theme of drug logos, dagusibu, and Beyorn Use Date (BUD) provided to respondents. In the Health examination, information was obtained, the respondents suffered from health problems as evidenced by the results of health checks, especially on blood pressure. In conclusion, education on pharmacy topics obtained satisfactory results for high school students